2020
DOI: 10.1371/journal.pbio.3000507
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between posttranslationally modified amino acids of methyl-coenzyme M reductase in Methanosarcina acetivorans

Abstract: The enzyme methyl-coenzyme M reductase (MCR) plays an important role in mediating global levels of methane by catalyzing a reversible reaction that leads to the production or consumption of this potent greenhouse gas in methanogenic and methanotrophic archaea. In methanogenic archaea, the alpha subunit of MCR (McrA) typically contains four to six posttranslationally modified amino acids near the active site. Recent studies have identified enzymes performing two of these modifications (thioglycine and 5-[S]-met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…Histidine and cysteine are possibly catalyzed by SAM-dependent N- and S-methyltransferases, respectively, while arginine and glutamine seem to have different enzymatic methylation ( Selmer et al, 2000 ). The methylation of cysteine and arginine have been shown to be related to a dedicated SAM-dependent (encoding by mcmA ) and a potential radical SAM-dependent methyltransferase (Mmp10, encoding by mmpX ); however, the enzyme for histidine and glutamine modification still remains unknown ( Deobald et al, 2018 ; Nayak et al, 2020 ). YcaO and TfuA were found to be involved in the biosynthesis of thioglycine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Histidine and cysteine are possibly catalyzed by SAM-dependent N- and S-methyltransferases, respectively, while arginine and glutamine seem to have different enzymatic methylation ( Selmer et al, 2000 ). The methylation of cysteine and arginine have been shown to be related to a dedicated SAM-dependent (encoding by mcmA ) and a potential radical SAM-dependent methyltransferase (Mmp10, encoding by mmpX ); however, the enzyme for histidine and glutamine modification still remains unknown ( Deobald et al, 2018 ; Nayak et al, 2020 ). YcaO and TfuA were found to be involved in the biosynthesis of thioglycine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was indicated that the biosynthesis of 1- N -methylhistidine and S -methylcysteine was probably catalyzed by SAM-dependent N - and S -methyltransferases by which the methyl group is transferred to N - or S -nucleophiles of histidine or cysteine via a S N 2 reaction. The gene ( mcmA ) encoding the SAM-dependent methyltransferase for cysteine methylation has been recently identified, and it has been indicated that cysteine methylation might play a role in adaption to mesophilic conditions ( Nayak et al, 2020 ). However, 2-( S )-methylglutamine and 5-( S )-methylarginine could not be formed by this mechanism ( Liscombe et al, 2012 ; Nayak et al, 2020 ).…”
Section: Post-translational Modifications Of Mcrsmentioning
confidence: 99%
See 3 more Smart Citations